Application of SPORT medical care model and nursing practice of hematopoietic stem cells collection for related donors of allogeneic hematopoietic stem cell transplantation (SPORT医疗照护模式下外周血造血干细胞移植亲缘供者干细胞采集的护理经验) - FU Xiaofeng (傅小凤); ZHU Liying (朱丽影) (中西医结合护理)
Objective To summarize the Application of SPORT medical care model and nursing practice of hematopoietic stem cells collection for related donors of allogeneic hematopoietic stem cell transplantation. Methods A retrospective analysis was conducted on 35 related donors of allogeneic hematopoietic stem cell transplantation whose hematopoietic stem cells were collected using Com. Tec cell separators from January 2022 to December 2023. Nursing interventions were provided during the blood cell collection process, including assessment, informed consent, preoperative preparation, operative cooperation, vascular access care, psychological nursing, observation of adverse reactions during the operation, and postoperative guidance, according to the SPORT(Screen-Preparation-Operation-rehabilitation-Transitional Care) medical care model. Results All donors successfully completed blood cell collection. There were five cases of mild toxic reaction to citrate, two cases of electrolyte disturbance, and two cases of hematoma at the puncture site. Targeted interventions were carried out to relieve the adverse effects. Conclusion The SPORT medical care model is helpful in improving the comfort of donors and ensuring that donors can complete stem cell collection procedures smoothly. It can also improve the success rate of collected stem cells and reduce the incidence of adverse reactions in donors. (目的 总结SPORT医疗照护模式下外周造血干细胞移植亲缘供者干细胞采集的护理经验。方法 收集2022年1月—2023年12月使用Com. Tec血细胞分离机进行干细胞采集的35名亲缘供者的临床资料, 基于SPORT医疗照护模开展早期筛查、早期准备、采集术中监测、术后康复指导以及延续护理, 积极预防并发症。结果 35名亲缘供者均顺利完成血细胞采集, 5名供者出现轻度枸橼酸盐中毒反应, 2名供者出现电解质紊乱, 2名供者出现穿刺部位血肿, 给予针对性干预, 不良反应均消除。结论 SPORT医疗照护模式有助于提高外周血造血干细胞被采集者的舒适度, 保证供者顺利完成干细胞采集术, 提高采集干细胞成功率, 同时降低供者不良反应的发生率。)